2006
DOI: 10.3847/aer2006001
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Collaborative Ranking Tasks on Student Understanding of Key Astronomy Concepts

Abstract: This research concerns the development and assessment of a program of introductory astronomy conceptual exercises called ranking tasks. These exercises were designed based on results from science education research, learning theory, and classroom pilot studies. The investigation involved a single-group repeated measures experiment across eight key introductory astronomy topics with 253 students at the University of Arizona. Student understanding of these astronomy topics was assessed before and after tradition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 25 publications
1
40
0
1
Order By: Relevance
“…Several studies have shown that students' abilities to perform well on multiple-choice questions have no significant relationship with their ability to perform well on essay tests [1][2][3]. Furthermore, in the discipline of astronomy education research, two studies revealed that when students were asked to provide explanations of the reasoning behind their multiple-choice responses, the majority of students provided insufficient evidence to match their correct multiple-choice response before and after instructional interventions [4,5]. A similar science education study comparing responses by Lee, Liu, and Linn showed that results from open-ended responses were more useful in determining the range and impact of an instructional intervention [6].…”
Section: A Background and Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that students' abilities to perform well on multiple-choice questions have no significant relationship with their ability to perform well on essay tests [1][2][3]. Furthermore, in the discipline of astronomy education research, two studies revealed that when students were asked to provide explanations of the reasoning behind their multiple-choice responses, the majority of students provided insufficient evidence to match their correct multiple-choice response before and after instructional interventions [4,5]. A similar science education study comparing responses by Lee, Liu, and Linn showed that results from open-ended responses were more useful in determining the range and impact of an instructional intervention [6].…”
Section: A Background and Motivationmentioning
confidence: 99%
“…In our study, we used similar methods of comparing multiple-choice and open-ended responses as these studies. We focused on the content area of celestial motions, investigating both similar and different concepts than those previously studied [4]. Unlike any of the other studies mentioned here, we also measured student performance at the end of the semester, in addition to before and after instruction.…”
Section: A Background and Motivationmentioning
confidence: 99%
“…Both studies illustrate that the development of research-based materials, implemented in a learner-centered classroom, can have a positive effect on student understanding of astronomy topics. The Ranking Tasks study, in particular, showed that these materials can be made such that initially low-achieving students can in the end score as high as initially high-achieving students post-instruction, and that these materials and assessments do not necessarily show the gender bias that has been observed in so many other materials (Hudgins, 2005).…”
Section: Call For Interactive Engagement Methods For Use In Astronomymentioning
confidence: 99%
“…If physics education research has been able to show that interactive engagement Similarly, Hudgins (2005) showed that regular use of Ranking Tasks in an ASTRO 101 course helped students to make significant learning gains beyond what was reached after lecture. Both studies illustrate that the development of research-based materials, implemented in a learner-centered classroom, can have a positive effect on student understanding of astronomy topics.…”
Section: Call For Interactive Engagement Methods For Use In Astronomymentioning
confidence: 99%
“…However, planetarium projections should be offered in addition to, not in place of, student-centered active inquiry using personal computers during laboratory classes. Hudgins et al (2006) and Ashcraft and Courson (2003) found significant improvement in preservice teacher scores linked to inquiry-based lab activities.…”
Section: Introductionmentioning
confidence: 99%